Correct Programming and Robust Queueing Theory in an Integrated Model for Quality-Of-Service Enhancement in Service Systems - Hasanain Hamed Ahmed (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This article presents a review study that proposes a blended model combining actual programming techniques with queuing theory to improve the performance and service quality of service systems. The main objective is to design a system that is capable of serving customers as efficiently as possible, using solutions derived from queuing theory to regulate and optimize customer flow, while applying accurate programming methods to ensure that the system operates correctly and in accordance with established standards. The study discusses how these two approaches complement each other and demonstrates that integrating them provides a balance between operational efficiency and the quality of services delivered. To illustrate the effectiveness of this hybrid model, a case study is examined to highlight the practical impact and real-world implications of the proposed framework. Both mathematical formulations and experimental analyses were employed to evaluate the model’s effectiveness. Findings indicate that this combined approach not only enhances system reliability but also provides measurable improvements in customer satisfaction and service outcomes. By offering a structured way to integrate queuing solutions with precise programming, this research contributes to the development of more sustainable and effective service management strategies. The model therefore has significant potential for broader application in industries that rely heavily on service delivery and customer flow optimization.